PENGARUH PENDIDIKAN NON-FORMAL TERHADAP PENINGKATAN PEMAHAMAN MODERASI BERAGAMA PADA JAMAAH PENGAJIAN SENIN DI PONPES SADANA - Mohammad Fikri Muthohhari; Muhammad Fakhrial Dewanda Zain; Hikmatul Luthfi (PT. Hasba Edukasi Mandiri, 2025)
This study examines the influence of non-formal education on enhancing the understanding of religious moderation among participants of the Monday study group at Pondok Pesantren Sadana. The issue of religious moderation has become increasingly crucial amid rising polarization and extremism that threaten social cohesion. As a traditional Islamic educational institution, the pesantren plays a strategic role in instilling inclusive and tolerant religious values. However, in-depth studies on the effectiveness of non-formal education conducted by pesantren—particularly routine study sessions—in shaping the understanding of religious moderation remain limited. The findings reveal that the non-formal education implemented by Pondok Pesantren Sadana has a positive and significant impact on improving the understanding of religious moderation among the Monday study group participants. Variables such as attendance intensity, the content delivered, and teaching methods show a strong correlation with indicators of religious moderation, including tolerance, anti-violence, acceptance of local traditions, and national commitment. These findings affirm that community-based non-formal education models, such as study groups in pesantren, are effective in shaping moderate religious character. The practical implication of this research highlights the importance of strengthening non-formal education programs in pesantren and other religious institutions as a preventive strategy against the spread of radical ideologies and to promote religious moderation values within the broader society.